2006
DOI: 10.2458/azu_jrm_v59i5_marsett
|View full text |Cite
|
Sign up to set email alerts
|

Remote Sensing for Grassland Management in the Arid Southwest

Abstract: We surveyed a group of rangeland managers in the Southwest about vegetation monitoring needs on grassland. Based on their responses, the objective of the RANGES (Rangeland Analysis Utilizing Geospatial Information Science) project was defined to be the accurate conversion of remotely sensed data (satellite imagery) to quantitative estimates of total (green and senescent) standing cover and bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 6 publications
0
16
0
Order By: Relevance
“…The addition of the NDVI and soil characteristics in addition to microwave observations to these models reduced the RMSE for soil moisture retrieval by 30% approximately. This also opens the discussion for use of more sophisticated vegetation indices such as Fractional Green Vegetation Cover, Green Leaf Area Index, and Soil Adjusted Total Vegetation Index [63,64] to differentiate vegetation and soil response in soil moisture retrieval using microwave remote sensing data. Validation results showed that fuzzy logic and neural network models performed better compared to multiple regression.…”
Section: Discussionmentioning
confidence: 99%
“…The addition of the NDVI and soil characteristics in addition to microwave observations to these models reduced the RMSE for soil moisture retrieval by 30% approximately. This also opens the discussion for use of more sophisticated vegetation indices such as Fractional Green Vegetation Cover, Green Leaf Area Index, and Soil Adjusted Total Vegetation Index [63,64] to differentiate vegetation and soil response in soil moisture retrieval using microwave remote sensing data. Validation results showed that fuzzy logic and neural network models performed better compared to multiple regression.…”
Section: Discussionmentioning
confidence: 99%
“…Due to the issue of cloud cover, a set of images was selected representing only nine months of the year 2014 (January, February, April, May, Jun, July, August, September, October). In order to improve the predictive capability for toxic metals in soils and as we assumed that vegetation cover may provide important information for soil toxic metals' spatial modeling, the following spectral indices were derived from the satellite images: BCI, biophysical composition index [43]; EVI, enhanced vegetation index [44]; LSWI, land surface water index [45]; NDVI, normalized differential vegetation index [46]; SATVI, soil-adjusted total vegetation index [47,48]; SAVI, soil-adjusted vegetation index [49]; TVI, transformed vegetation index [50]; WDVI, weighted difference vegetation index [51,52]; and tasseled cap transformation including brightness, greenness and wetness [53]. The formulas used to derive these indices are shown in Table 2.…”
Section: Remote Sensing Images and Spectral Indicesmentioning
confidence: 99%
“…Early determination of the distribution and severity of rapidly spreading invasive populations of musk thistle is needed to implement mitigation treatments, but accurate assessments are often difficult or impossible to obtain with ground surveys, because of the extensive land area involved, time and labor required and inaccessibility of many areas [25][26][27]. Therefore, remote sensing has received considerable attention as a rapid, inexpensive and non-destructive method for assessing non-native noxious species invasions [6,27].…”
Section: Introductionmentioning
confidence: 99%